Penatalaksanaan Holistik Pasien Vertigo dan Dispepsia Fungsional Pada Ny. M Usia 37 Tahun di Puskesmas Rawat Inap Gedong Air Melalui Pendekatan Kedokteran Keluarga - Adilla Dwi Nur Yadika; Sahab Sibuea (Majority, 2022)
Vertigo is a false perception of a person's movements or the surrounding environment. Dyspepsia is a collection of symptoms of the upper digestive tract disorders. This case report aims to implement a holistic and comprehensive approach of a family doctor and patient management based on evidence based medicine, patient-centered, family oriented and community oriented. Primary data was obtained through autoanamnesis, physical examination and home visits. Secondary data was obtained from the patient's medical record. Assessment based on a a qualitative and quantitative holistic diagnosis. The results obtained are patients suffering from vertigo and dyspepsia with internal risk aspects such as inappropriate diet and eating habits, often late to eat, likes to consume spicy, sour, and fried foods, curative treatment patterns, and lack of knowledge about the disease. The external risk aspects are the lack of family knowledge about the patient's illness and curative family treatment patterns. Holistic management of patients and families through poster about the diseases suffered by patients, exercise that can be done by the patient, regular eating patterns, and foods that can cause the symptoms. At the time of evaluation, the patient had no symptoms anymore. The conclusions of the case report are holistic management can increase knowledge and change the patient’s behaviour and the role and support of the family are needed in the treatment of the patient. Keywords: Family doctor, functional dyspepsia, holistic treatment, vertigo.